Identificação de bactérias lácticas presentes em amostras de pingos das regiões da serra da canastra e da serra do salitre utilizando métodos dependentes e independentes de cultivo - César Lúcio Lopes de Faria Júnior (2007)
Natural starter cultures (pingos) are essential to development of chesse flavor, and they are used in a empirical way during the manafacture of artisanal Minas cheese produced in the regions of Serra da Canastra and Serra do Salitre. The objective of this work was to identify the bacterial community present in pingo samples from Serra da Canastra and Serra do Salitre by dependent and independent-cultivation methods. Pingo samples were collected from three farms at each region. The species identified in high counting number by dependent culture method at Serra da Canastra were: Lactococcus lactis, Bacillus cereus and Bacillus cereus – like, at farm A; Lc. lactis and B. cereus-like, at farm B; B. cereus and B. cereus-like, at farm C. At Serra do Salitre, prevalent species were Lc. lactis and B. cereus-like at the three farms studied. On the other hand, by independent-cultivation method the species found at Serra da Canastra (two farms were sampled by this method) were: Lc. lactis and Streptococcus salivarius, at farm A; Lc. lactis, B. cereus, Macrococcus caseolyticus, Lactobacillus casei, Leuconostoc mesenteroides and a species similar to uncultured bacteria (EF051484- Genbank number), at farm B. In the two farms studied by this method in Serra do Salitre, prevalent species were: Lc. lactis and a species like an uncultured bacterial clone (AY668120 – GenBank number), at farm D; Lc. lactis, Lactococcus garviae, Le. mesenteroides, Vagococcus carniphilus and the uncultured bacterial clones similar to those deposited in GenBank with accession numbers EF071401, AY911184, AY960268, DQ343062 and DQ342413, were obtained at farm E. The comparison between frequency of species identified by cultivation dependent method and that obtained by independent-cultivation method showed significant difference among the species composition of bacterial communities present in pingos at same region and from different regions.